Alternative protein blends as a replacement for fish meal in diets for white seabass, Atractoscion nobilis. (19th December 2014) - Jirsa, D.; Barrows, F.T.; Hardy, R.W.; Drawbridge, M.
Abstract: An 8‐week feeding trial was conducted to determine the effectiveness of replacing fish meal (FM) with blends of alternative proteins in diets for white seabass (WSB, Atractoscion nobilis ) at a starting weight of 5.6 g. Five diets were formulated with 400–440g kg −1 crude protein (380g kg −1 digestible). These included a high 520g kg −1 FM control diet, a series of three diets with a sequential replacement of FM containing 410g kg −1, 510g kg −1 and 630g kg −1 of a soy‐based protein blend (SPC) and 200g kg −1, 100g kg −1 and 0g kg −1 FM, respectively and a fifth diet containing 550g kg −1 of a corn‐based protein blend (CGM) and 100g kg −1 FM. Survival was highest in the FM control group at 99% but all other performance measures (weight gain, feed conversion ratio, specific growth rate and protein retention efficiency) were worse than the other treatment groups. Weight gain reached a maximum of 595% in the SPC 200g kg −1 FM treatment group. Performance decreased as inclusion of the soy‐based protein blend increased. The CGM treatment performed comparably to the SPC 100g kg −1 FM treatment among all measures, except for survival, which was higher in the CGM 100g kg −1 FM treatment. With nutrient levels and alternative protein blends used in this study, FM can be reduced to 100g kg −1 of the diet for WSB without reductions in performance.